710 Magnetic Resonance Imaging Versus Ultrasonography in Assessing Changes in Fat Liver Content in Obese Children After One-Year Nutritional Intervention. (October 2012) - Verduci, E; Pozzato, C; Radaelli, G; Rovere, A; Salvioni, M; Banderali, G; Riva, E; Giovannini, M
Abstract : Background and Aims: Despite the potential clinical and practical relevance, there is lack of studies in current literature assessing the relationship of longitudinal change of liver fat content with liver biochemical parameters in paediatric age. The aim of the present study was to assess whether any association may exist of change in liver fat content based on MRI with change in liver biochemical parameters in obese children who underwent a one-year nutritional intervention. Methods: Fourthy six obese children, aged 6–14 years, underwent metabolic measurements, liver ultrasonography (US) and chemical-shift MRI examinations at baseline and after an one-year nutritional intervention. Biochemistry included serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Liver fat fraction (FF) on MRI was judged elevated as it was 39%. Results: Prevalence of FF³ 9% declined from 34.8% to 8.7% ( P <0.01), with a mean (95%CI) reduction of 7.8 (5.0–10.6)%. At baseline, FF was associated with any liver biochemical parameters (maximum P <0.001). At the end of intervention association was found with AST ( P =0.017). Change of FF was associated with change in AST ( P =0.027) and ALT( P =0.024). Liver echogenicity was associated with ALT at baseline (P <0.001). An age and sex adjusted multiple regression analysis showed that FF change was independently associated with change in serum AST (adjusted regression coefficient 0.348, P =0.048). Conclusions: The results suggest that in obese children undergoing nutritional interventions longitudinal changes in liver fat content may be associated with change in serum transaminases suggesting novelty in monitoring NAFLD in childhood obesity.